Sexual Stimulants: Prevalence and Associated Factors Amongst Married Women in Sokoto Metropolis, Sokoto State, Nigeria - U. M. Ango; M. O. Oche; M. M. Bello; E. U. Yunusa; M. T. Umar; A. Adamu; B. H. Adamu; S. M. Adetoro; D. T. Shija (Archives of Current Research International, 2021)
Aim: This study was aimed at assessing the prevalence and factors associated with the use of sexual stimulants (aphrodisiacs) among married women in Sokoto metropolis, Sokoto state, Nigeria. Methodology: A cross-sectional study was conducted among 215 married women in Sokoto metropolis selected by multistage sampling technique. A set of pre-tested, semi-structured interviewer- administered questionnaire was used to collect data on the research variables. Data were analyzed using IBM® SPSS version 20 statistical package. Results: A total of 215 married women were interviewed, out of which 209 were aware of sexual stimulants. Of the 209 respondents who were aware of sexual stimulants, majority 183 (85.0%) reported using one form of sexual stimulants or the other and up to 135 (73.8%) of those who used sexual stimulants were from monogamous setting, their main source of information concerning sexual stimulants was from family relatives 101 (55.2%). A large proportion of the respondents 127 (69.4%) used it to satisfy their spouses while majority (84.3%) of them reported increased sexual pleasure/satisfaction by them and their husbands. Complications developed by the respondents while using sexual stimulants include: vaginal itching 8(30.8%), vaginal discharge 5(19.2%), dryness of the vagina and irregular menstrual period 2 (7.7%) each, vaginal bruises, lower abdominal pain and painful intercourse 3 (11.5%) each. Conclusion: The study revealed a high prevalence of use of sexual stimulants among the respondents, with the substances being obtained from various sources and used for different reasons. A sizeable number of them opined that they used the substances to enhance their sexual satisfaction and that of their husbands. Since the pharmacological compositions of these substances have not been ascertained, there is need for community education on the health risks associated with the use of sexual stimulants as some of them may have adverse effects on the organs of the body.